Effects of different gasification biochar grain size on greenhouse gases and ammonia emissions in municipal aerated composting processes. (1st April 2023) - Ottani, Filippo; Parenti, Massimiliano; Santunione, Giulia; Moscatelli, Giuseppe; Kahn, Rocky; Pedrazzi, Simone; Allesina, Giulio
Abstract: This work is aimed at investigating the effects derived from the application of minimum amounts of two different sized biochars, obtained through biomass gasification, on the greenhouse gases and ammonia emissions from a co-composting process of the organic fraction of municipal solid waste. The chosen biochar-to-organic waste share is set to 3% w/w dry, and the results obtained are compared with a conventional composting process without biochar. Nine aerated static pilot-scale bins with a volume of 1.3 m 3 were prototyped and run, three per thesis and three for the control. The trial lasted 63 days, following the same approach used in full-scale composting facilities. The testing period was divided into a forced aeration phase followed by a static phase. In terms of global warming potential, the use of fine biochar and coarse biochar resulted in 13 and 11 kg CO2 eq ton-1 emitted respectively. These values are 36% and 45% lower than the 20 kg of CO2 eq ton-1 emitted by the control theses. Specifically, the chosen minimum amounts of biochar produced a reduction of CH4 and N2 O, while a significant reduction in NH3 emissions was not detected. Carbon dioxide showed a slight increase in biochar theses. This work has proven that fine and coarse gasification-derived biochars improve the bio-oxidative phenomena and reduce greenhouse gases emissions of the composters, regardless of the biochar particle size and regardless of the modest 3% w/w biochar-to-organic waste share used. Graphical abstract: Image 1 Highlights: Two grain sizes of biochar are added at 3% w/w to an organic waste compost process. Decomposition greenhouse-gases are measured to see the biochar impact on the emission. Biochar significantly reduced methane and nitrous oxide emissions. The coarse biochar reduces emissions in term of CO2 equivalent up to 45%. Improved final product with high carbon and mineralized nitrogen content is obtained.